Age and benefit of early coronary angiography after out-of-hospital cardiac arrest in patients presenting with shockable rhythm: Insights from the Sudden Death Expertise Center registry. (July 2018) - Aissaoui, Nadia; Bougouin, Wulfran; Dumas, Florence; Beganton, Franckie; Chocron, Richard; Varenne, Olivier; Spaulding, Christian; Karam, Nicole; Montalescot, Gilles; Aubry, Pierre; Sideris, Georges; Marijon, Eloi; et al.
Abstract: Background: Little is known about the association between provision of post-resuscitation care and prognosis of out-of-hospital cardiac arrest (OHCA) in elderly patients. Previous studies have suggested futility after 65 years of age. Objectives: We aimed to evaluate the association of early coronary angiogram (CAG) followed if necessary by percutaneous coronary intervention (PCI), with favorable outcome after OHCA among elderly patients, compared to younger patients. Methods: Using a large French registry, we included all OHCA patients with an initial shockable rhythm, transported to hospital from 2011 to 2015. Favorable outcome was defined as hospital discharge with Cerebral Performance Category (CPC) 1 or 2. and were evaluated by multivariate logistic regression. Subgroup analyses were performed according to age groups: <65, 65–75 and >75 years. Results: Among 1502 included patients, 31% were older than 65 and 12% older than 75 years. An early CAG was performed in 79%, 88% and 76% of patients below 65, between 65 and 75 and above 75, respectively (P = 0.002). The rate of patients discharged with CPC1 or 2 was 42% below 65, 38% between 65 and 75 and 24% above 75 (P < 0.001). Among the whole population, early CAG (OR = 6.4, 95% CI = 3.9–10.5, P < 0.001) was associated with favorable outcome. In subgroups analysis, CAG was associated with favorable outcome among patients <65 and 65–75. In patients >75, there was a trend towards a favorable outcome (OR2.9, 95CI = 0.9–9.1). Conclusions: In a large registry of OHCA survivors, the early CAG use was associated with a better prognosis. This benefit was persistent up to 75 years of age, suggesting that age alone should not guide the decision for early invasive strategy.